Flawless - Silver, Elsie (Naperville, Illinois : Bloom Books, 2023)
Rhett Eaton is the face of professional bull riding. The golden boy. Or at least he was until it all blew up in his face after a public brawl. Now his agent says he has to clean up his image, and sticks Rhett with his ball-busting daughter for the rest of the season as "full-time supervision." But Rhett doesn't need a babysitter--especially one with skin-tight jeans, a sexy smirk, and a mouth she can't stop running. And he quickly learns that Summer Hamilton isn't just another conquest. She sees the man behind the mask, and she doesn't run--she pulls him closer, even when she shouldn't. She says this means nothing. Rhett says this means everything. She says there are boundaries they shouldn't cross. That Rhett's reputation can't take any more hits...and neither can her damaged heart. Rhett says he's going to steal it anyway. -- Back cover.
"Originally self-published in 2022 by Elsie Silver" -- Title page verso.
Keywords: Bull riders -- Fiction; Man-woman relationships -- Fiction; Ranches -- Fiction; Reputation -- Fiction; Canada -- Fiction; Romance fiction